The Effect of Marketing Mix 4P on Purchasing Decisions and Repurchasing Intention Prochiz in Indonesia Using the SEM and SWOT Methods - Nugroho, Aqshal Daffa; Waluyo, Minto (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
Prochiz comes as a delicious cheese product, with high nutritional content. Prochiz has problems with product, price, place, and promotion variables on purchasing decisions and repurchase intention. In addition, Prochiz is still ranked 2nd in the Top Brand Index ranking, and has not been able to become number 1. The purpose of this study was to determine the effect of the 4P marketing mix on purchasing decisions and repurchases of Prochiz cheese in Indonesia and determine the marketing strategy of Prochiz cheese using the SWOT (Strengths, Weaknesses, Opportunities, and Threats) method. The method used in this study uses SEM (Structural Equation Modeling) and SWOT. SEM is used to show simultaneous equations between variables and SWOT is used to determine marketing strategies. The results of data processing show that the product has a significant effect on repurchase intention, while the price and place variables doesn’t have a significant effect on purchasing decisions, promotion cannot be proven, and purchasing decisions have a significant effect on repurchase intention. The simultaneous equation obtained in this study is Y1 = 0,839 X2 + 0,167 X2 + 0,005 X3 + Z4 and Y2 = 0,727 X1 + 0,147 X2 + 0,004 X3 + Z5.